Effect of Different Denture Base Materials and Changed Mouth Temperature on Dimensional Stability of Complete Dentures - Khalid A. O. Arafa (International Journal of Dentistry)
Background. Type of materials used in fabrication of denture base has an effect on dimension during denture base material processing and other factors related to clinical use. Objective. The study aims were to assess the dimensional stability including thermal changes of three different denture base materials. Methods. Ninety patients were selected to construct complete dentures with different denture base materials. They were randomly divided into three groups: group 1, patients with cobalt chrome metallic base; group 2, patients with heat curing acrylic resin fabricated by injection moulding technique; and group 3, patients with denture bases fabricated by conventional heat curing acrylic resin. The dimensional changes were assessed using digital caliper. Results. After the twelfth month, injection moulding acrylic resin had significantly the highest dimensional change followed by the conventional heat curing acrylic resin. There were no significant differences in the dimensions between the three types of denture base materials at normal mouth temperature, while, after hot tea drinking at 45°C, the dimensional change was significantly the highest in cobalt chrome metallic denture base group. Conclusion. Cobalt chrome metallic denture base has stable dimension compared to denture bases fabricated of acrylic resin but it was more affected by altered mouth temperature. The study was registered in the International Standard Randomized Controlled Trials Number (ISRCTN) registry with study ID (ISRCTN94238244).